2020
DOI: 10.21203/rs.3.rs-74778/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Prevalence of Chronic Kidney Disease in Hypertensive Patients in Primary Care in Hong Kong: A Cross-Sectional Study

Abstract: BackgroundTo identify the prevalence of Chronic Kidney Disease (CKD) in Chinese hypertensive population managed in a local public primary care clinic and to explore its associated risk factors. MethodsMedical records of Chinese adult hypertensive patients (> 18 years of age) who had been followed up in a public general outpatient clinic (GOPC) from 1 Jan 2018 to 30 Jun 2018 were retrieved and reviewed, and a sample group was randomly selected. Demographic, clinical parameters including age, gender, smoking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(15 reference statements)
1
0
0
Order By: Relevance
“…SCys C, an alternative marker with few limitations, was examined and compared to SCr. One of the most infective CKD can occur in any age group, and these results agree with [24] who found that mean ages group of (40-49) years was largest these results agreed with [25] Moreover, other studies that agreed with this study were done by [26], who reported a mean age of (50 -≥ 60) years The gender disparity in CKD patients may be explained by the fact that females in these studies may have had greater than males [27]. The higher rate of CKD infection among females may be due to CKD risk factors such as hypertension, diabetes, proteinuria, renal anatomy, and change hormones, which have been observed to have differing impacts on men and women [28].…”
Section: Discussionsupporting
confidence: 89%
“…SCys C, an alternative marker with few limitations, was examined and compared to SCr. One of the most infective CKD can occur in any age group, and these results agree with [24] who found that mean ages group of (40-49) years was largest these results agreed with [25] Moreover, other studies that agreed with this study were done by [26], who reported a mean age of (50 -≥ 60) years The gender disparity in CKD patients may be explained by the fact that females in these studies may have had greater than males [27]. The higher rate of CKD infection among females may be due to CKD risk factors such as hypertension, diabetes, proteinuria, renal anatomy, and change hormones, which have been observed to have differing impacts on men and women [28].…”
Section: Discussionsupporting
confidence: 89%